1990
DOI: 10.1364/josaa.7.001847
|View full text |Cite
|
Sign up to set email alerts
|

X-ray holographic microscopy using photoresists

Abstract: Gabor x-ray holograms of biological specimens and of test objects that display <56-nm resolution are presented. This spatial resolution is more than an order of magnitude smaller than what has been achieved previously in x-ray holography. The holograms were recorded on photoresist using 2.57-nm soft x rays from the X-17t undulator at the National Syncrotron Light Source at Brookhaven National Laboratory. The processed photoresists were enlarged with an electron microscope and digitized using a scanning microde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…The obtained resolution exceeds by~19-21 nm the best possible obtainable resolution of 27 nm set by l 2NA [10]. Several factors degrade the resolution.…”
Section: Gaussian Filtering and Correlation Methods For Resolution Andmentioning
confidence: 82%
See 1 more Smart Citation
“…The obtained resolution exceeds by~19-21 nm the best possible obtainable resolution of 27 nm set by l 2NA [10]. Several factors degrade the resolution.…”
Section: Gaussian Filtering and Correlation Methods For Resolution Andmentioning
confidence: 82%
“…Gabor holography with an early X−ray laser pumped by two beams of the fusion−class NOVA laser at Law− rence Livermore National Laboratory demonstrated a spatial resolution of 5 μm [9]. Other experiments utilized synchrotron light to image biological samples, nano structures, and magnetic domains [10][11][12]. Lens−less diffractive imaging based on iterative phase retrieval following the proposal by Sayre [13] has demonstrated soft X−ray imaging with 50−nm spatial resolu− tion utilizing l = 1.5 nm source [14].…”
Section: Developments In High Resolution Euv and Soft X-ray Holographmentioning
confidence: 99%
“…Gabor holography with an early X-ray laser pumped by two beams of the fusion-class NOVA laser at Lawrence Livermore National Laboratory demonstrated a spatial resolution of 5 m (Trebes et al, 1987). Other experiments utilized synchrotron light to image biological samples, nano structures, and magnetic domains (Jacobsen et al, 1990;Lindas et al, 1996;McNulty et al, 1992). Lensless diffractive imaging, based on iterative phase retrieval, following the proposal by Sayre, (Sayre et al, 1998) have demonstrated SXR imaging with 50 nm spatial resolution utilizing = 1.5 nm source (Elsebitt et al, 2004).…”
Section: Developments In High Resolution Euv and Soft X-ray Holographmentioning
confidence: 99%
“…The first demonstration of holographic recording using a EUV/SXR laser was performed in Lawrence Livermore National Lab, using the NOVA laser facility [3]. Some early experiments also utilized large facilities synchrotron light to image biological samples, nano structures, and magnetic domains [4,5]. The first demonstration of holo− graphic imaging using a table−top source achieved 7−μm spatial resolution with a high harmonic (HHG) source [6].…”
Section: Introductionmentioning
confidence: 99%